INHIBITION OF FOULING BACTERIA BY THE MARINE EPIPHYTES FROM SELECTED LOCATIONS IN MALAYSIA - Supardy, Nor Afifah; Ibrahim, Darah; Mat Nor, Sharifah Radziah; Md Noordin, Wan Norhana; Ismail, Ahmad (Malaysian Journal of Science, 2017)
The rising demand for natural antifouling agents has led to the search for potential secondary metabolites from marine epiphytic bacteria. The objective of this study is to isolate the epiphytic bacteria from various marine invertebrates and to screen for their antibacterial activities against a list of fouling bacteria. In this study, the antibacterial activity of 91 epiphytic bacteria were tested against 21 fouling bacteria. In the preliminary screening of the inhibition activity, the fouling bacteria were cross-streaked with the epiphytic bacteria. Isolates with prominent inhibitory activity (susceptible fouling bacteria â‰¥ 40%) were subjected to fermentation for five days, and their cell-free supernatants were extracted with ethyl acetate (1:1 v/v) to obtain the crude extracts. In the secondary screening, the extracts were tested against fouling bacteria via the disc diffusion assay. At 2.00 mg/disc, 12 out of 30 extracts were effective against at least one fouling bacteria. Two most outstanding antibacterial activities were demonstrated by isolates PD4.8 and PD4.9, which were isolated from Caulerpa racemosa. Isolate PD4.8 was effective against five fouling bacteria with the largest inhibition zone of 16.0 mm, whilst PD4.9 was effective against four fouling bacteria with the largest inhibition zone of 15.0 mm. This study demonstrated a significant antibacterial activity of epiphytic isolates PD4.8 and PD4.9 against the fouling bacteria, and should be further investigated for production of antifouling compound. ABSTRAK Peningkatan permintaan terhadap agen anti-penempelan semulajadi telah membawa kepada pencarian metabolik sekunder yang berasal daripada bakteria laut. Objektif kajian ini adalah untuk memencilkan bakteria epifit daripada pelbagai invertebrata laut dan untuk menguji aktiviti antibakteria mereka terhadap bakteria penempelan. Dalam kajian ini, akitiviti anti-bakteria oleh 91 bakteria epifit yang dipencilkan daripada invertebrata laut diuji terhadap 21 bakteria penempel. Dalam pemeriksaan awal aktiviti perencatan, bakteria penempel dicoretkan bersilang dengan bakteria epifit. Pencilan dengan aktiviti perencatan yang menonjol (bakteria penempelan terkesan â‰¥ 40%) diteruskan dengan proses penapain selama lima hari, dan supernatan yang bebas dari sel diekstrak dengan etil asetat (1:1 v/v) untuk mendapatkan ekstrak mentah. Dalam pemeriksaan sekunder, ekstrak mentah diuji terhadap baketeria penempel melalui asai cakera penyebaran. Pada kepekatan 2.00 mg/ml, 12 daripada 30 ekstrak didapati berkesan terhadap sekurang-kurangnya satu bakteria penempel. Dua pencilan yang menunjukkan aktiviti perencatan paling ketara ialah pencilan PD4.8 dan PD4.9 yang berasal daripada Caulerpa racemosa. Pencilan PD4.8 berkesan terhadap lima bakteria penempelan dengan zon perencatan tertinggi 16.00 mm, manakala pencilan PD4.9 berkesan terhadap empat bakteria penempel dengan zon perencatan tertinggi 15.00 mm. Kajian ini telah mendedahkan aktiviti anti-bakteria yang ketara oleh pencilan epifit PD4.8 dan PD4.9 terhadap bakteria penempelan dan kajian harus diteruskan untuk memencilkan sebatian semulajadi dengan aktiviti anti-penempelan.